Collaborative study from the Bladder Cancer Advocacy Network for the genomic analysis of metastatic urothelial cancer - Damrauer, Jeffrey S.; Beckabir, Wolfgang; Klomp, Jeff; Zhou, Mi; Plimack, Elizabeth R.; Galsky, Matthew D.; Grivas, Petros; Hahn, Noah M.; O’Donnell, Peter H.; Iyer, Gopa; Quinn, David I.; Vincent, Benjamin G.; et al. (Nature communications, 2022)
Urothelial Cancer - Genomic Analysis to Improve Patient Outcomes and Research (NCT02643043), UC-GENOME, is a genomic analysis and biospecimen repository study in 218 patients with metastatic urothelial carcinoma. Here we report on the primary outcome of the UC-GENOME—the proportion of subjects who received next generation sequencing (NGS) with treatment options—and present the initial genomic analyses and clinical correlates. 69.3% of subjects had potential treatment options, however only 5.0% received therapy based on NGS. We found an increased frequency of TP53 E285K mutations as compared to non-metastatic cohorts and identified features associated with benefit to chemotherapy and immune checkpoint inhibition, including: Ba/Sq and Stroma-rich subtypes, APOBEC mutational signature (SBS13), and inflamed tumor immune phenotype. Finally, we derive a computational model incorporating both genomic and clinical features predictive of immune checkpoint inhibitor response. Future work will utilize the biospecimens alongside these foundational analyses toward a better understanding of urothelial carcinoma biology. The Bladder Cancer Advocacy Network established the UC-GENOME study in order to create a biobank and data repository for metastatic urothelial carcinoma. Here, the authors present the first characterization and analysis of DNA and RNA sequencing data from the 218 patients included in the UC-GENOME.